THE EFFECT ON KNOWLEDGE AND ATTITUDE LEVELS OF FAMILY PLANNING EDUCATION GIVEN TO SYRIAN REFUGEE WOMEN - GÜMÜŞ ŞEKERCİ , Yasemin and AYDIN YILDIRIM, Tuğba (Göbeklitepe Medical Science Journal, 2022)
The use of family planning services prevents about one in three pregnancy-related deaths and 44% of neonatal deaths. The study was conducted with the aim of assessing the effectiveness of family planning education given to refugee women coming from Syria to Hatay province in Turkey. The research was planned as a quasi-experimental study with a non-randomized control group and a pre/post-test design. The experimental group were interviewed at the beginning, right after training and after one month. The control group were not given education. A personal information form, a Family Planning Information Form, and the Family Planning Attitude Scale were used to collect data. Data analysis was performed with the use of frequencies, percentages, means, minimum and maximum values, medians, standard deviations, the chi-square test, and the paired sample t test. After providing education to the Syrian refugee women, family planning knowledge and attitudes had significantly improved in the experimental group compared to the control group (p<0.05). The family planning education program, which was given while taking into account cultural considerations and native language, significantly developed the women’s knowledge and attitudes. It was recommended that family planning education programs should be included in all clinics focusing on women’s health.